(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Background: Birth weight is the single most crucial criterion for determining neonatal and infant survival, hence investigations on risk factors that lead to this condition are critical. This study aimed to maternal factors responsible for delivering low birth weight (LBW) babies in Bangladesh. Methods: This case-control study was conducted at the Obstetrics and Gynaecology ward, BIRDEM general Hospital. All procedures were performed in accordance with the Declaration of Helsinki and informed consent was obtained from all subjects. Fifty mothers of LBW babies (<2500 g) were considered as cases, while 150 mothers of normal birth weight (2500- 4000 g) babies were enrolled as controls. Data were collected from both hospital record and direct interview by researcher herself. Data were recorded in separated case record form and analyzed by SPSS 24. Results: Maximum mothers (74.7%) from control group were aged ≤ 30 years at delivery, while maternal age of 50% cases were >30 years (p=0.001). Multivariate logistic regression analysis found that para ≥ 3 (AOR=3.63, 95% CI= 1.10-11.96, p=0.034), preterm labor (AOR=3.28, 95% CI= 1.50-7.16, p=0.003), gestational hypertension (AOR=2.87, 95% CI= 1.22-6.77, p=0.016) and pre-mature rupture of membrane (PROM, AOR=3.22, 95% CI= 1.10-9.37, p=0.032) were the independent maternal factors for LBW baby. However, gestational diabetes mellitus, anaemia, previous history of CS, hypothyroidism, UTI, vaginal candidiasis, polyhydramnios and oligohydramnios had no such association with LBW. Conclusion: Para ≥ 3, preterm labor, gestational hypertension and PROM are the significant maternal factors for LBW babies. Bangladesh J Obstet Gynaecol, 2021; Vol. 36(2): 101-106